Professional communication skills needed by students in preparing a career: contribution to achieving the SDGs - Tarigan, Surya Setiadi; M. Djami, Reysanti; Arianci Lubalu, Maria Petronela (Institute of Computer Science (IOCS), 2024)
This study aimed to identify the professional communication skills required by students in preparing for their career and the contribution of these skills to achieving the Sustainable Development Goals (SDGs). The research applied descriptive qualitative method using questionnaire to collect the data. The sample of this research was consisted of 70 final-year students of business administration students at Kupang State Polytechnic. The questionnaires were distributed to measure students' perceptions about the professional communication skills needed in preparing their career in the workplace and their contribution to the SDGs. The results indicated that the professional communication skills for verbal and written were in “required” category, it meant that the students needed to improve the public speaking ability such as presentation, handling a phone and conference, networking, and negotiation skills. Moreover, the written communication or business writing skill such as letter, memo, and repot needed by the students too. Those skills necessity must be overcome by giving training so the graduates are ready getting a good career in the workplace. Mastering the professional communication skills were not only crucial for individual career success but also significantly contributes to achieving sustainable development goals (SDGs), particularly in areas such as quality education (Goal 4) and Partnerships for the Goals (Goal 17). The study concluded that bridging the communication skills gap is imperative for preparing a future workforce capable of driving sustainable development and achieving global goals